Tsukuba International Environmental Art Symposium '85 : Indoor Exhibitions - Outdoor Exhibitions - Panel Discussions. (Tsukuba : City of Tsukuba, 1985)
Abe, Hiroyasu ; Issiki, Kunihiko ; Ito, Kosho ; Ito, Takamichi ; Ito, Hiroshi ; Inomoto, Taku ; Iwashita, Kyoko ; Iwase, Kyoko ; Endo, Kazuko ; Otsuki, Takayuki ; Ohashi, Atsushi ; Ohira, Tomohiro ; etc.
Tsukuba International Environmental Art Symposium '85: Indoor Exhibitions - Outdoor Exhibitions - Panel Discussions, 1985.6.1. - 9.16
English-Japanese
kunstcatalogus